Diagnostic Accuracy of the Triglyceride-Glucose (TyG) Index for Identifying Advanced Chronic Kidney Disease in Type 2 Diabetes: A Cross-Sectional Analysis - Mathias Wahyu Manumpak Lumbantobing; Nindia Sugih Arto; Sylvia Youvella; Ricke Loesnihari; Mohammad Riza Lubis; Ranti Permata Sari (HM Publisher, 2026)
Background: Chronic kidney disease (CKD) is a debilitating microvascular complication of type 2 diabetes mellitus (T2DM), fundamentally exacerbated by systemic insulin resistance and glucolipotoxicity. The triglyceride-glucose (TyG) index is emerging as a practical surrogate for insulin resistance. This study aims to evaluate the diagnostic accuracy of the TyG index in identifying advanced CKD among adults with T2DM. Methods: A cross-sectional analysis was conducted on 44 adult T2DM patients with CKD at a tertiary referral hospital. To establish an adequate diagnostic threshold, advanced CKD was explicitly defined as an estimated glomerular filtration rate (eGFR) < 30 mL/min/1.73 m2 (Stages IV and V). Patients were statistically stratified into three equal tertiles based on their TyG index. Diagnostic performance was evaluated using the Receiver Operating Characteristic (ROC) curve analysis. Results: The median eGFR demonstrated a severe, statistically significant decline across increasing TyG tertiles (Tertile I: 54.09; Tertile II: 36.42; Tertile III: 19.12 mL/min/1.73 m2; p < 0.001). ROC analysis revealed a strong diagnostic profile for identifying advanced CKD, yielding an Area Under the Curve (AUC) of 0.756 (95% CI: 0.595–0.916, p = 0.002). An optimal cut-off value of 8.81 provided a sensitivity of 89.5% (95% CI: 66.9–98.7%), a specificity of 60.0% (95% CI: 38.7–78.9%), a positive predictive value of 63.0% (95% CI: 42.4–80.6%), and a negative predictive value of 88.2% (95% CI: 63.6–98.5%). Conclusion: The TyG index is strongly associated with renal decline in T2DM. It serves as a highly accessible, adjunctive screening tool to stratify patients at risk for severe renal impairment.